Avaliação de propriedades de superfície da liga Ti-35Nb-7Zr-5Ta submetida à anodização e seus efeitos n adesão bacteriana - Carneiro, Haline de Lima [UNESP] (2014)
The aim of this study was to compare the surface properties and the adhesion of Streptococcus mutans on Ti-35Nb-7Zr-5Ta and commercially pure titanium (cp Ti) before and after the anodization. Discs (Ø8mmx2mm, N=40) were divided into 2 groups: T (cp Ti), TNZT (Ti-35Nb-7Zr- 5Ta), and subdivided in untreated (A- , control) or anodic treated (A+) in β- glicerofostato + calcium acetate (300 V, 1min). The evaluated surface properties were: surface topography and qualitative identification of chemical elements (in scanning electron microscope -SEM/EDS), surface free energy (SFE, measured with a goniometer), and the average roughness (Radetermined in profimoleter). The discs were contaminated with Streptococcus mutans (NTCC 25175) for determination of CFU/mL; the surfaces with adhered viable cell were also analyzed with SEM. The values of Ra and ELS were compared (A- vs . A+) by means of Kruskal-Wallis associated Dun test (α= 0.05). The median Ra (μm) and ELS (mN/m), respectively, were: A- T=0.97/44.24; TNZT=0.17/36.68; A+ T=1.21/56.88; TNZT=0.53/ 53.64. All groups showed significantly higher values of Ra and ELS (p < 0.05) after anodizing. The analysis in SEM/EDS indicated the formation of a multiporous layer with deposition of Ca and P ions. Only anodic treated TNZT exhibited an increase in adhesion of S. mutans. It was concluded that the anodic tretament of Ti cp and TNZT change the surface properties with potential improvements for osseointegration, despite the increase in the adhesion of S. mutans on TNZT.